DEVELOPMENT OF DOMINO CARD AS A LEARNING MEDIA IN HUMAN MOTION SYSTEM FOR CLASS VIII MTs STUDENTS - Mohammad Misbakhul Fatikh; Nur Kuswanti (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
This research is motivated by the difficulty of students in understanding the material of the Human Skeleton System and the teacher has untapped the learning media to the maximum so that learning seems boring and students prefer learning while playing. It needs to development of innovative learning media. This research aimed to produce learning media in the form of Domino Cards on the material of the Human Motion System for students of class VIII MTs / SMP that are appropriate based on validity, practicality and effectiveness. This research is a type of development research using the ADDIE development model which consists of five stages of development namely Analyze, Design, Develop, Implement, and Evaluate. Media trial subjects are 20 students of MTs. Ar-Rohman Laban. The instruments used include the Domino Card media validation sheet, the Domino Card media usage sheet, and the posttest question sheet. The average score obtained from the validator is 3.88 with category